Co-creation Tourism Experience in Perceived Usability of Interactive Multimedia Features on Mobile Travel Application - Lee, Angeline; Siti Shukhaila, Shaharuddin; Ng, Edmund Giap Weng; Syaryfah Fazidawaty, Wan Busrah (UTEM, 2017)
The aim of this paper is to explore the use of interactive multimedia features on mobile travel services to improve touristic experiences. This study delivered a workable prototype with visiting Sarawak as a case study by integrating locality/authenticity design and interactive multimedia features content. User-testing was carried out to identify whether the mobile application usability can improve visitor experiences. A total of 40 visitors (18 male and 22 female) were recruited to participate in the user-testing study. The results indicated a positive SUS score 81 out of 100 and that multimedia interactivity on mobile travel application could enrich tourist’s co-creation experiences compared to just static navigation and limited interaction. The outcome also significantly enhanced tourism experiences through authenticity design attractions such as iconicity and heritage elements value of a destination region. Overall, the findings provide perception of how tourists perceived usability of interactive mobile travel application and the impact of interface motif. Implications and suggestion are further discussed in this paper.